FEATURES OF WORK AND SCOPE OF APPLICATION OF CRUSHED STONE MASTIC EXPANSION JOINTS OF BRIDGE STRUCTURES - I. F. Khikmatova, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The paper discusses various aspects of the use of crushed stone-mastic expansion joints in bridge structures, describes the main existing problems and ways to solve them. The experience of application, advantages and disadvantages of this type of expansion joints are given, as well as the scope of their application at the current stage of bridge construction development is outlined.